Исследование теплообмена в пучках профилированных труб - Кузнецов, В. В.; Якимович, А. В. (Eastern-European Journal of Enterprise Technologies, 2009)
Results of research of heat exchange in banks of the profiled pipes with small longitudinal and back pitches are presented. Criteria dependences for calculation of heat transfer processes are verification. Results of comparison of heat transfer efficiency in the profiled and bare-tube banks of pipes are obtained